Validation of ELISA with recombinant antigens in serological diagnosis of canine Leishmania infantum infection - Mahyumi Fujimori; Arleana do Bom Parto Ferreira de Almeida; Stella Maria Barrouin-Melo; Luiz Ricardo Paes de Barros Cortez; Malcolm Scott Duthie; Roberto Mitsuyoshi Hiramoto; Flaviane Alves de Pinho; Steven Gregory Reed; Valéria Régia Franco Sousa; Nazaré Fonseca Souza; Rodrigo Martins Soares; José Eduardo Tolezano; et al. (Memorias do Instituto Oswaldo Cruz, 2021)
BACKGROUND Dogs are the main peridomiciliary reservoir of Leishmania infantum thus the correct diagnosis of infection is essential for the control of the transmission and treatment as well. However, the diagnosis is based on serological assays that are not fully effective. OBJECTIVE We aimed to establish an effective serological assay for the diagnosis of L. infantum infected dogs using Leishmania-derived recombinant antigens. METHODS Leishmania derived rK39-, rK28-, rKR95-based enzyme-linked immunosorbent assay (ELISA) was standardized using symptomatic and asymptomatic L. infantum-infected dogs. Then 2,530 samples from inquiry in endemic areas for VL were evaluated and the results compared with recommended assays by the Brazilian Ministry of Health (MH algorithm). Further samples from a cohort of 30 dogs were searched. FINDINGS For rK39-, rK28- and rKR95-ELISA the sensitivity was around 97% and specificity 100%. The positivity of these three ELISA in the inquiry samples was 27-28%, around 10% higher than the assays currently in use. When cohort samples were searched, we observed likely false-negative results (> 65%) with supposedly negative samples that turned positive six months later with the assays in use (MH algorithm). MAIN CONCLUSIONS For the diagnosis of L. infantum-infected dogs, rK39-based ELISA showed better diagnostic performance than other assays in use in Brazil and worldwide.